Experimental study of the light absorption in sea water by thermal lens spectroscopy. (January 2016) - Velásquez, A; Sira, E; Silva, S; Cabrera, H
Abstract: Thermal lens spectroscopy is well known as highly sensitive technique enabling measurements of low absorption and concentration determination of various compounds. The optical absorption coefficients of doubly distilled water and samples of water from different places of the open Ocean and different coastal regions have been measured at 532.8 nm wavelength using this technique. The method enables sensitive, rapid and reproducible determination of small variations of the absorption coefficient which are related with small trace contaminations in sea water.